Leveraging Digital Finance for Driving Sustainable Economic Growth in Nigeria - Shehu, Ummi Rahama; Yahaya, Usman Shehu (Kashere Journal of Education, 2025)
This study aims to explore Leveraging Digital Finance for Driving Sustainable Economic Growth in Nigeria. This research explores the significance of digital finance and its potential impact on Nigeria’s economy. It aims to assess how digital finance influences economic growth, financial inclusion, and stability. Using a positivist approach, the study involved 384 participants, with data analysed through regression analysis to identify the relationships between digital finance and key economic outcomes. The study also tested three null hypotheses, all of which yielded rejections, thereby confirming strong connections between digital finance and sustainable development indicators. The Technology Acceptance Model (TAM) formed the theoretical foundation, offering insights into how users accept and adopt digital finance solutions. Additionally, the Capability Approach Theory was used to examine how digital finance can enhance individual capabilities and overall well-being. Ultimately, the research highlights the role of digital finance in fostering sustainable development in Nigeria and provides valuable recommendations for policymakers, financial institutions, and other stakeholders. The study advocates for greater adoption of digital finance to promote economic growth, financial inclusion, and stability in the country.